2012
DOI: 10.1091/mbc.e11-10-0831
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of Fcj1 is required for formation of crista junctions and interacts with the TOB/SAM complex in mitochondria

Abstract: The molecular mechanisms determining mitochondrial architecture are largely unclear. The C-terminal domain of Fcj1 and the TOB complex are shown to interact. Both are important for determining cristae morphology. The results explain how crista junctions are positioned at the outer membrane, assigning novel functions to both Fcj1 and the TOB complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
104
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 34 publications
6
104
0
8
Order By: Relevance
“…In human cells, mitofilin was found to interact with the sorting and assembly machinery of the outer membrane (SAM complex) that has a central role in the biogenesis of outer membrane proteins ( Figure 2B) (Xie et al , 2007 ;Darshi et al , 2011 ;Alkhaja et al , 2012 ;Ott et al , 2012 ). In yeast, interactions of mitofilincontaining protein complexes of the inner membrane with the SAM complex, the TOM complex, porin channels and Ugo1 have been reported (Figure 2A) (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;K ö rner et al, 2012 ;Zerbes et al , 2012 ). The interaction of mitofilin with the TOM complex was shown to support the import of precursor proteins into the intermembrane space via the mitochondrial intermembrane space assembly (MIA) machinery (von der Malsburg et al , 2011 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 98%
See 4 more Smart Citations
“…In human cells, mitofilin was found to interact with the sorting and assembly machinery of the outer membrane (SAM complex) that has a central role in the biogenesis of outer membrane proteins ( Figure 2B) (Xie et al , 2007 ;Darshi et al , 2011 ;Alkhaja et al , 2012 ;Ott et al , 2012 ). In yeast, interactions of mitofilincontaining protein complexes of the inner membrane with the SAM complex, the TOM complex, porin channels and Ugo1 have been reported (Figure 2A) (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;K ö rner et al, 2012 ;Zerbes et al , 2012 ). The interaction of mitofilin with the TOM complex was shown to support the import of precursor proteins into the intermembrane space via the mitochondrial intermembrane space assembly (MIA) machinery (von der Malsburg et al , 2011 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 98%
“…These findings have prompted the hypothesis of a structural and functional connection between contact sites and crista junctions. The possibility of such an overlapping localization has been repeatedly addressed, although never comprehensively clarified (van der Klei et al , 1994 ;Perkins et al , 1997 ;Reichert and Neupert , 2002 ;Harner et al , 2011 ;K ö rner et al, 2012 ). Some studies have suggested that the integrity of crista junctions may depend on their anchoring to the outer mitochondrial membrane via mitofilin-containing contact sites (Harner et al , 2011 ;K ö rner et al, 2012 ;Ott et al , 2012 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
See 3 more Smart Citations